2016
DOI: 10.1039/c6cp03823a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and molecular dynamics studies of anthraquinone dyes in a nematic liquid-crystal host: a rationale for observed alignment trends

Abstract: Five anthraquinone dyes with bis(4-propylphenyl) substituents, connected via sulfide or amine linking groups at the 1,5-positions or directly at the 2,6-positions, have been studied as guests in the nematic liquid crystal host, E7. Polarized UV-visible absorption spectra of aligned samples were used to obtain experimental dichroic order parameters, which exhibit values in the range 0.51-0.74. Fully atomistic MD simulations of these guest-host systems were carried out, generally using default parameters but usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 88 publications
4
24
0
Order By: Relevance
“…The average values over the last 500 ns of the simulations, given in Table 4, suggest that all three dye molecules exhibit lower molecular order parameters than the host molecules, which is consistent with the less rod-like shapes of the dye molecules. In our previous work, we observed that the trend in the calculated order parameters of the host molecules in guest-host mixtures matched that of the guest molecules, and that is the case again for these simulations [31], demonstrating that the addition of guest molecules has an influence on the calculated alignment of the overall mixture.…”
Section: Simulationssupporting
confidence: 71%
See 1 more Smart Citation
“…The average values over the last 500 ns of the simulations, given in Table 4, suggest that all three dye molecules exhibit lower molecular order parameters than the host molecules, which is consistent with the less rod-like shapes of the dye molecules. In our previous work, we observed that the trend in the calculated order parameters of the host molecules in guest-host mixtures matched that of the guest molecules, and that is the case again for these simulations [31], demonstrating that the addition of guest molecules has an influence on the calculated alignment of the overall mixture.…”
Section: Simulationssupporting
confidence: 71%
“…In particular, the relationship between the molecular structure and the dichroic order parameter is not always intuitive. A general approach to understanding this complex relationship has been provided by our recent development of computational methods to aid in dye design [29][30][31][32]. We have shown that a novel combination of molecular dynamics (MD) simulations and time-dependent density functional theory (TD-DFT) calculations, based on the application of Equation (4), can provide a rationale for observed trends in order parameters from calculations of S θ and S β that are combined to give values of S ϕ that are directly comparable with experimental values of S. These methods have resulted in the successful prediction of order parameter trends for 1,5-and 2,6-disubstituted anthraquinones dyes and have demonstrated that the choice of principal molecular axis, which affects calculations of both S θ and S β , may have a significant influence on the calculated dichroic order parameter [32].…”
Section: Introductionmentioning
confidence: 99%
“…2. 41,42 In parallel, we demonstrated that a combination of fully atomistic MD simulations of the guest-host systems and time-dependent density functional theory (TD-DFT) calculations on optimised structures of the dye molecules could be used to obtain calculated dichroic order parameters, S f , that are directly comparable with the experimental values, and which we used to rationalise the trend observed experimentally between the dyes. In these studies, the principal molecular axes were defined as the minimum MOI axes, providing consistency with other reported MD studies, and the molecular order parameters, S y (MOI), were calculated from the MD simulations according to eqn (1) for the host and according to the first term in eqn (2) for the guest dyes.…”
Section: Introductionmentioning
confidence: 84%
“…2 Structures and abbreviations of the five anthraquinone dyes studied in this work, along with the respective S exptl values we reported previously. 41,42 axes may not be defined readily by symmetry. The work reported here extends our studies of the set of five anthraquinone dyes in the nematic host E7, which provide a useful data set to assess some general assumptions that are often made about molecular axis systems, and for which the results may be expected to have wider relevance than these particular systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation